2020
DOI: 10.1097/cce.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastography to Detect Hypercoagulability and Reduced Fibrinolysis in Coronavirus Disease 2019 Acute Respiratory Distress Syndrome Patients

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Reduced fibrinolytic activity was also observed in patients with COVID-19, with all studies reporting LY30 less than 1%, including three which showed complete fibrinolytic shutdown (LY30 of 0%) [ 18 , 23 , 25 ]. A shortened R-time of less than 5 min was observed in patients from four studies [ 18 , 20 , 22 , 26 ], indicating a shorter time to clot formation in hypercoagulable patients, although the R-value was within the range of normal in most studies ( Figure 4 ), implying that the change in R-time is less consistent than the increased MA [ 5 , 14 , 15 , 19 ] and fibrinolytic shutdown in the characterization of COVID-19. Platelet function, measured by the PlateletMapping ADP assay, was in the high normal range for the majority (81%) of patients with COVID-19 in the one study where this parameter was measured [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reduced fibrinolytic activity was also observed in patients with COVID-19, with all studies reporting LY30 less than 1%, including three which showed complete fibrinolytic shutdown (LY30 of 0%) [ 18 , 23 , 25 ]. A shortened R-time of less than 5 min was observed in patients from four studies [ 18 , 20 , 22 , 26 ], indicating a shorter time to clot formation in hypercoagulable patients, although the R-value was within the range of normal in most studies ( Figure 4 ), implying that the change in R-time is less consistent than the increased MA [ 5 , 14 , 15 , 19 ] and fibrinolytic shutdown in the characterization of COVID-19. Platelet function, measured by the PlateletMapping ADP assay, was in the high normal range for the majority (81%) of patients with COVID-19 in the one study where this parameter was measured [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…VETs were performed using ROTEM (25 studies), TEG (15 studies), Quantra (two prospective studies [66,67]) and ClotPro (one retrospective study [24] and one case report [68]); no study compared two devices. Among articles reporting data about TEG, four were prospective studies [52,[59][60][61], ten were retrospective studies [51,[53][54][55][56][57][58][62][63][64], and one was a case report [65]. Among articles dealing with ROTEM, thirteen were prospective studies [28][29][30][31][32][39][40][41][42][43][44][45][46], seven were retrospective studies [27,[33][34][35][36]48,49], one was a cross-sectional study [47], and four were case reports [26,37,38,50].…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…Testing was carried out either on admission or within the following days, but the timing of blood collection for VET was specified only for 29 studies [24,26,27,[29][30][31]33,[35][36][37][38]41,[43][44][45][46][47][48]50,53,[55][56][57][58][59][65][66][67]. In some studies, the measurements were repeated during the patientʹs stay, either because of a pre-established protocol [26,27,29,45,53,59,60,67] or because of the occurrence of a thromboembolic event [65,68].…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A group including one of the authors (PK) recently published a case series of TEG studies from the first wave of COVID-19 patients encountered which consistently revealed hypercoagulability with rapid and large amplitudes of clot formation with little to no fibrinolytic activity present. 80,81 These early insights, along with the large amount of subsequent investigations reviewed below, served as an initial basis for the more aggressive anti-coagulation regimen incorporated within MATHþ.…”
Section: Anticoagulation and Covid-19mentioning
confidence: 99%